ПРІОРИТЕТИ БЮДЖЕТНОЇ ПОЛІТИКИ УКРАЇНИ ПОРІВНЯНО З ЗАГАЛЬНОЄВРОПЕЙСЬКИМИ ТЕНДЕНЦІЯМИ - Затонацька, Тетяна Георгіївна; Лаврентьєв, Максим Миколайович (Науковий журнал «Світ фінансів», 2017)
Затонацька Т. Г.,  Лаврентьєв М. М. Пріоритети бюджетної політики України порівняно із загальноєвропейськими тенденціями. Висвітлено пріоритетні напрями бюджетної політики в Україні за 2012–2015 рр. порівняно з 28 країнами ЄС. Проаналізовано видатки Зведеного бюджету України за головними функціями та видатки Зведеного бюджету України на економічну діяльність. Досліджено розподіл загальних державних видатків за головними функціями на економічну діяльність у країнах ЄС. Проведено порівняльний аналіз цілей бюджетної політики України та країн ЄС. Запропоновано пріоритетні напрями спрямування фінансових ресурсів держави в умовах економічної кризи, а саме – на розвиток стратегічно важливих для країни сегментів економіки (транспортна галузь, агропромисловий комплекс, паливно-енергетичний комплекс у напрямку енергозбереження та зниження енергоємності). Затонацкая Т. Г.,  Лаврентьев М. Н. Приоритеты бюджетной политики Украины в сравнении с общеевропейскими тенденциями. Показаны приоритетные направления бюджетной политики в Украине за 2012–2015 гг. по сравнению с 28 странами ЕС. Проанализированы расходы Сводного бюджета Украины по главным функциям и расходы Сводного бюджета Украины на экономическую деятельность. Исследовано распределение общих государственных расходов по главным функциям на экономическую деятельность в странах ЕС. Проведён сравнительный анализ приоритетов бюджетной политики Украины и стран ЕС. Предложены приоритетные направления финансовых ресурсов государства в условиях экономического кризиса, а именно – на развитие стратегически важных для страны сегментов экономики (транспортная отрасль, агропромышленный комплекс, топливно-энергетический комплекс в направлении энергосбережения и снижения энергоёмкости). Zatonatska T., Lavrentiev M. The priorities of the budget policy of Ukraine in comparison with European trends. Introduction. The limitation of financial resources in the public sector of Ukraine necessitates, on the one hand, clearly defined priority areas for their use, funding of which will ensure reaching the strategic aims of development of the state, and on the other hand, the reduction of budget expenditures. The article highlights the priority areas of fiscal policy in Ukraine for the period of 2012–2015 years compared to the 28 EU countries. Budget expenditures of Ukraine on the main functions were analyzed during the period of 2012–2015 years and also budget expenditures of Ukraine on economic activity during the period of 2012–2015 years. The priority directions of state aid for certain economic activities were analyzed in details.Purpose. The article aims to identify priority areas of budget financing in order to reach the effective use of scarce financial resources and provide economic development of the state. Methods. An abstract-logical method was applied while determining the structure of the work and the scheme of construction of the research. A systematic approach made it possible to examine the tools of fiscal adjustment of national economy comprehensively and to identify the most significant links between fiscal policy of Ukraine and the 28 EU countries. The methods of statistical analysis were used.Results. The distribution of total public expenditures on primary functions and the distribution of total public expenditures on economic activity in the EU countries were analyzed. Comparative analysis of priorities of budget policy of Ukraine and the EU was made, which stated that the order of the main budget priorities in Ukraine doesn’t differ a lot from the one in the EU countries. Meanwhile, differences in the quantitative meaning of the share of GDP that is spent on performing of the basic functions of the state are great. Differences in the areas of expenditures on economic activity were identified. First of all, it is the priority of public spending on energy sector in Ukraine, in contrast to the development of transport in the EU-28. Secondly, it is insignificant spending on: the overall economic and trading activities and employment; basic and applied research and development in the fields of economy in Ukraine, which is a national priority in the EU countries.Conclusion. Priority areas for channeling financial resources of the state in the economic crisis, namely the development of strategically important segments of the country’s economy (transport industry, agriculture, fuel and energy complex in the area of energy conservation and reducing energy intensity) were proposed.